2009
DOI: 10.1111/igc.0b013e31819914c5
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Characteristics of Malignant Germ Cell Tumors in the Ovaries of Korean Women: A Korean Gynecologic Oncology Group Study

Abstract: From January 1995 to December 2000, medical records of 196 patients were collected from 14 hospitals nationwide and were reviewed retrospectively. We evaluated the clinicopathologic characteristics of malignant germ cell tumors in the ovaries of South Korean women and determined the prognostic factors affecting recurrence. The mean patient age was 23.8 years (range, 4-63 years), and the median follow-up period was 67 months (range, 1-128 months). The distribution of the International Federation of Gynecology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 17 publications
1
19
0
3
Order By: Relevance
“…9 About 75% of dysgerminoma affect the women below 30 years of age and they are extremely rare after the age of 50. 7,10,12 Lee et al reported the mean age of women in their study as 23.8 years ( Range 4-63 years ) 11 ,a finding similar to our case. Most of the ovarian neoplasms are asymptomatic and are often diagnosed on clinical examination or picked up on grey scale sonography.…”
Section: IIIsupporting
confidence: 87%
“…9 About 75% of dysgerminoma affect the women below 30 years of age and they are extremely rare after the age of 50. 7,10,12 Lee et al reported the mean age of women in their study as 23.8 years ( Range 4-63 years ) 11 ,a finding similar to our case. Most of the ovarian neoplasms are asymptomatic and are often diagnosed on clinical examination or picked up on grey scale sonography.…”
Section: IIIsupporting
confidence: 87%
“…Epithelial cell tumors represent the majority of all ovarian neoplasms (82%) (1). Conversely, germ cell tumors (GCTs) are rare, comprising approximately 20% of all ovarian tumors, both benign and malignant ones (1,2). Approximately 3-5% of ovarian GCTs are malignant (2).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, germ cell tumors (GCTs) are rare, comprising approximately 20% of all ovarian tumors, both benign and malignant ones (1,2). Approximately 3-5% of ovarian GCTs are malignant (2). The most commonly occurring GCTs is dysgerminoma, which accounts for approximately 2% of all ovarian cancers (2).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations